2022
DOI: 10.3390/agronomy12102463
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision and Deep Learning for Precision Viticulture

Abstract: During the last decades, researchers have developed novel computing methods to help viticulturists solve their problems, primarily those linked to yield estimation of their crops. This article aims to summarize the existing research associated with computer vision and viticulture. It focuses on approaches that use RGB images directly obtained from parcels, ranging from classic image analysis methods to Machine Learning, including novel Deep Learning techniques. We intend to produce a complete analysis accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 161 publications
0
14
0
1
Order By: Relevance
“…PV can only be effective if the right quantity and quality of data are available and are properly processed and interpreted. Although machine learning and artificial intelligence are rapidly evolving [ 75 ], the role of the human factor in the decision-making process is still significant. The quality of wine particularly depends on the human factor [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…PV can only be effective if the right quantity and quality of data are available and are properly processed and interpreted. Although machine learning and artificial intelligence are rapidly evolving [ 75 ], the role of the human factor in the decision-making process is still significant. The quality of wine particularly depends on the human factor [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study may have some intersection with Chen et al [24], which aimed to review studies that used deep learning for plant image identification. Besides, Mohimont et al [25] reviewed studies that used computer vision and DL for yield-related precision viticulture tasks, e.g. flower counting, grape detection, berry counting and yield estimation, while Ferro and Catania [26] surveyed the technologies employed in precision viticulture, covering topics ranging from sensors to computer vision algorithms for data processing.…”
Section: Of 34mentioning
confidence: 99%
“…Flower counting, grape detection, berry counting, yield estimation, disease identification and variety identification are examples of such tasks. Mohimont et al [25] analysed recent precision viticulture studies that applied DL techniques to all of the above yield-related tasks, excluding variety identification and disease detection. The number of studies the authors found for each task individually does not differ from the number of studies found in the present study.…”
Section: Comparison With Other Subfields Of Precision Viticulturementioning
confidence: 99%
“…We must also not forget that the visible color is the result of an interaction between the spectrum of the emitted light and the surface. If a white sheet is illuminated by the light of a red bulb, then the sheet will also appear red [29].…”
Section: Search Subject By Bloommentioning
confidence: 99%